Maeroan atomic investigations on the skull of chinchilla lanigera - Sadullah BAHAR; Aysun ÇEVİK DEMİRKAN; Vural ÖZDEMİR; İsmail TÜRKMENOĞLU (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was investigated the bones which formed the skull in chinchilla and compared the results with other rodents and same carnivores. Material and method: In this study, 10 adult chinchilla (S female. 5 male) were used. The animals were euthanatized by ordinary methods, Maceration method was used to show skull Result: It was observed that the important features of skull were a wide orbita, long and sharp incisive tooth, and well developed tympanic bulla at the behind of parietal bones. Protuberantia occipitalis externa was well developed and crista facialis was absent. Dental formula was found as II CO P1 M3 in upper and lower jaw. In conclusion, becomes a member of suborder of Rodentia. Chinchilla has nearly same macroanatomic features of bones which consist of skull like their relatives such as Squirrel and Hystrix cristata.